Positive electrode active material, battery monomer, battery device and electric device

By coating lithium nickel manganese oxide and doping elements on the surface of lithium phosphate and combining it with a carbon coating layer, the problem of low compaction density of lithium-ion battery positive electrode active materials was solved, and the battery energy density and performance were improved.

CN120637465AActive Publication Date: 2025-09-12JIANGSU CONTEMPORARY AMPEREX TECH LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202511116502.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-11
Publication Date
2025-09-12
Estimated Expiration
2045-08-11

AI Technical Summary

Technical Problem

Existing lithium-ion battery positive electrode active materials, such as lithium-containing phosphates, have the problem of low compaction density, which affects the energy density of the battery.

Method used

By coating lithium nickel manganese oxide on the surface of lithium-containing phosphate, a tightly arranged Ni/Mn-O octahedral structure is formed to increase the compaction density of the material. The structural stability and lithium ion migration performance of the material are improved by doping elements such as titanium and magnesium. At the same time, a carbon layer is coated on the surface to improve conductivity.

Benefits of technology

The compaction density and conductivity of the positive electrode active material are significantly improved, the energy density and rate performance of the battery are enhanced, and polarization and side reactions are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120637465A_ABST
    Figure CN120637465A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode active material, a battery monomer, a battery device and a power utilization device. The positive electrode active material comprises an inner core and a first coating layer arranged on at least part of the surface of the inner core, the inner core comprises lithium manganese iron phosphate; the first coating layer comprises lithium nickel manganese oxide. And by coating the lithium nickel manganese oxide, the overall compaction density of the positive electrode active material is improved, and the battery performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode active material, a battery cell, a battery device, and an electrical device. Background Art

[0002] Secondary batteries represented by lithium-ion batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] The positive electrode active material has a significant impact on battery performance. Lithium-containing phosphates are promising positive electrode active materials, but they have problems such as low compaction density to a certain extent. Summary of the Invention

[0004] The purpose of the present application is to provide a positive electrode active material, a battery cell, a battery device and an electrical device. The positive electrode active material has a good compaction density, which is conducive to improving the energy density of the battery.

[0005] To this end, a first aspect of the present application provides a positive electrode active material comprising a core and a first coating layer disposed on at least a portion of the surface of the core; The core includes a lithium-containing phosphate; The first coating layer includes lithium nickel manganese oxide.

[0006] By coating lithium nickel manganese oxide (LNO) on the surface of lithium-containing phosphate, the compaction density of the positive electrode active material can be significantly improved. LiNO crystals are composed of tightly packed Ni / Mn-O octahedra. The metal atoms have a small radius, forming a highly symmetrical cubic structure with a high atomic packing density and a high compaction density. Therefore, coating lithium-containing phosphate with LNO helps to increase the overall compaction density of the composite material.

[0007] In some embodiments, the lithium-containing phosphate includes lithium manganese iron phosphate.

[0008] Compared with lithium iron phosphate, lithium manganese iron phosphate replaces some of the Fe elements in the lattice sites with Mn elements, which can greatly increase the charge and discharge voltage of the material, which is beneficial to improve the energy density of the material. However, due to the difference in the radius of manganese and iron ions in lithium manganese iron phosphate, there are gaps between the particles in the lattice, and the compaction density is relatively low (usually 2.2~2.5g / cm 3 By coating lithium nickel manganese oxide with a higher compaction density, the compaction density of the composite positive electrode active material can be significantly improved.

[0009] In some embodiments, the lithium manganese iron phosphate contains at least one of titanium and magnesium.

[0010] Titanium doping can occupy iron or manganese sites, forming stable tetravalent cation centers in the lithium manganese iron phosphate material lattice, improving the material's structural integrity during charge and discharge cycles. Magnesium doping can lengthen the Li-O covalent bond length in the LiO6 octahedron, facilitating lithium ion migration and improving the battery's rate performance.

[0011] In some embodiments, the chemical formula of the lithium manganese iron phosphate is as shown in Formula 1: Li 1+a (Mn x1 Fe y1 M1 z1 M2 1-x1-y1-z1 )PO4 formula 1 Among them, -0.2≤a≤0.2, 0<x1<1, 0<y1<1, 0≤z1≤0.05, 0≤1-x1-y1-z1≤0.05; M1 includes at least one of Ti and Mg, and M2 includes at least one of Al, Cu, Zn, Ni, V, Zr, Co, Ga, Sn, Sb, and Nb.

[0012] The above chemical formula can be used to represent the lithium manganese iron phosphate in the positive electrode active material, showing the stoichiometric range of each element and possible doping elements. The fluctuation range of the lithium stoichiometric number (1+a) (-0.2≤a≤0.2) is due to the lithium insertion and removal behavior of the material during the battery's charge and discharge processes. The lithium manganese iron phosphate with the above chemical formula has a well-structured lattice structure and exhibits excellent electrochemical performance.

[0013] In some embodiments, the particle size Dv50 of the positive electrode active material is 300 nm to 600 nm.

[0014] When the above Dv50 is adopted, it is more conducive to achieving close packing to improve the compaction density. It is also beneficial to the dispersion of the slurry, has good adaptability to the existing roller pressing process, and has good coating uniformity.

[0015] In some embodiments, the lithium nickel manganese oxide contains at least one of the following elements: aluminum, phosphorus, and tungsten.

[0016] Aluminum doping improves the material's electronic conductivity. The high Al-O bond energy mitigates structural collapse, reduces Mn dissolution, and forms a stable SEI layer. Phosphorus doping improves the material's surface structural stability and also enhances the surface electronic conductivity of the positive electrode active material. Tungsten doping enhances the material's structural stability, forming a spinel phase on the surface, reducing surface oxygen content, strengthening the chemical bond between transition metals and oxygen, inhibiting the H2-H3 phase transition, and reducing the formation of microcracks.

[0017] In some embodiments, based on the total mass of the core and the first coating layer, the mass of the lithium nickel manganese oxide accounts for 0.8% to 2.5%.

[0018] In general, as the mass proportion of lithium nickel manganese oxide increases, the coating layer formed on the surface of lithium iron manganese phosphate becomes more uniform and stable, which is conducive to improving the compaction density of the composite material. However, the theoretical specific capacity of lithium nickel manganese oxide is lower than that of lithium iron manganese phosphate. Therefore, when the mass proportion of lithium nickel manganese oxide is high, the overall capacity of the composite material will be reduced to a certain extent. When lithium nickel manganese oxide has the above mass proportion, it can better balance the improvement of compaction density and the overall specific capacity of the material.

[0019] In some embodiments, based on the total mass of the core and the first coating layer, the mass of the lithium nickel manganese oxide accounts for 1% to 1.8%.

[0020] When lithium nickel manganese oxide has the above-mentioned mass ratio, it is beneficial to better balance the improvement of compaction density and the overall specific capacity of the material.

[0021] In some embodiments, the positive electrode active material further includes a second coating layer, the second coating layer includes carbon; the second coating layer is disposed on the surface of the first coating layer and / or on the surface of the core not covered by the first coating layer.

[0022] Carbon coating can improve the overall electronic conductivity of the composite material, thereby improving the electrical connection between materials during the battery's charge-discharge cycle, reducing polarization, and improving the material's rate performance. Furthermore, carbon coating reduces direct contact between the active material and the electrolyte, minimizing side reactions; it also mitigates the dissolution of transition metal ions (such as manganese ions) during high-temperature cycling, reducing side reactions caused by transition metal dissolution.

[0023] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of carbon element is 0.8% to 2%.

[0024] When the mass proportion of carbon elements is greater than or equal to 0.8%, the second coating layer has a more obvious effect on improving the overall conductivity of the composite material and can significantly reduce the resistivity of the powder; when the mass proportion of carbon elements does not exceed 2%, the lithium manganese iron phosphate can correspondingly have a higher mass proportion, which is conducive to the composite material having a good gram capacity.

[0025] In some embodiments, the powder compaction density of the positive electrode active material under a pressure of 30,000 N is 2.35 g / cm 3 ~2.7g / cm 3 .

[0026] The positive electrode active material in the embodiment of the present invention has the aforementioned relatively high compaction density, so when used in the positive electrode of a battery, a relatively high positive electrode sheet compaction density can be achieved, which is beneficial for improving the energy density of the battery.

[0027] In some embodiments, the powder resistivity of the positive electrode active material is less than or equal to 80 Ω·cm.

[0028] The positive electrode active material in the embodiment of the present invention has the above-mentioned good powder resistivity. When applied to the positive electrode of a battery, it is beneficial to form a good conductive network, reduce polarization, and improve rate performance.

[0029] In the second aspect of the present application, a battery cell is provided, comprising a positive electrode sheet, an electrolyte and a negative electrode sheet; the positive electrode sheet comprises a positive electrode collector and a positive electrode material layer arranged on at least one surface of the positive electrode collector; the positive electrode material layer comprises the positive electrode active material in any embodiment of the first aspect of the present application.

[0030] In some embodiments, the compaction density of the positive electrode material layer is 2.3 g / cm 3 ~2.5g / cm 3 .

[0031] By adopting the aforementioned positive electrode active material, the positive electrode material layer can have the above-mentioned compaction density, which is beneficial for the battery to have excellent energy density.

[0032] In a third aspect of the present application, a battery device is provided, comprising a battery cell according to any embodiment of the second aspect of the present application.

[0033] In a fourth aspect of the present application, an electrical device is provided, comprising a battery cell in any embodiment of the second aspect of the present application, or a battery device in any embodiment of the third aspect of the present application.

[0034] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Various other advantages and benefits will become apparent to those skilled in the art by reading the detailed description of the preferred embodiment below. The accompanying drawings are only for the purpose of illustrating the preferred embodiment and are not to be considered as limiting the present application. In the accompanying drawings: Figure 1 is a schematic diagram of a battery cell according to an embodiment of the present application; Figure 2 yes Figure 1An exploded view of a battery cell according to an embodiment of the present application is shown; Figure 3 is a schematic diagram of a battery module according to one embodiment of the present application; Figure 4 is a schematic diagram of a battery pack according to one embodiment of the present application; Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown; Figure 6 is a schematic diagram of an electrical device using a battery cell as a power source according to one embodiment of the present application; Figure 7 is a transmission electron microscope (TEM) image of the positive electrode active material provided in one embodiment of the present application; Description of reference numerals: 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 end cover. DETAILED DESCRIPTION

[0036] The exemplary embodiments of the present disclosure will be described in more detail below. It should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. Instead, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0037] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if minimum range values ​​1 and 2 are listed, and maximum range values ​​3, 4, and 5 are listed, then the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, stating that a parameter is an integer ≥ 2 is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0040] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, it is mentioned that the method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0041] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0042] Secondary batteries, represented by lithium-ion batteries, have been widely used. Lithium-containing phosphates, such as lithium iron phosphate and lithium manganese iron phosphate, are promising cathode active materials. However, they suffer from issues such as low compaction density.

[0043] The present application mainly improves the compaction density of the material by providing a coating layer containing lithium nickel manganese oxide on the surface of the lithium-containing phosphate, thereby improving the battery performance.

[0044] The solutions described in the embodiments of the present application are applicable to positive electrode active materials, battery cells using the positive electrode active materials, battery devices using the battery cells, and electrical devices using the battery cells or battery devices.

[0045] positive electrode active material In some embodiments of the present application, a positive electrode active material is provided, comprising a core and a first coating layer disposed on at least a portion of the surface of the core; The core includes a lithium-containing phosphate; The first coating layer includes lithium nickel manganese oxide.

[0046] By coating lithium nickel manganese oxide (LNO) on the surface of lithium-containing phosphate, the compaction density of the positive electrode active material can be significantly improved. LiNO crystals are composed of tightly packed Ni / Mn-O octahedra. The metal atoms have a small radius, forming a highly symmetrical cubic structure with a high atomic packing density and a high compaction density. Therefore, coating lithium-containing phosphate with LNO helps to increase the overall compaction density of the composite material.

[0047] The above-mentioned positive electrode active materials can be tested by methods commonly used in the art. For example, 0.2g of positive electrode material is weighed into a 100mL beaker, 10mL of 10% w / w nitric acid solution is added, and after heating and digesting at 120°C for 0.5 hours, the volume is fixed with a 100mL volumetric flask; then 1mL is pipetted into a 100mL volumetric flask and fixed to volume to obtain a test solution. An inductively coupled plasma optical emission spectrometer (ICP-OES, instrument brand: Agilent 5800) is used to determine the mass fraction of lithium, manganese, iron, phosphorus, doping elements, etc. in the test solution; the molar proportion of each element in the positive electrode material is calculated based on the mass fraction of each element in the powder test solution, thereby determining the chemical formula and element molar ratio of the positive electrode material.

[0048] In some embodiments, the lithium-containing phosphate includes lithium iron phosphate and lithium manganese iron phosphate.

[0049] In some embodiments, the lithium-containing phosphate includes lithium manganese iron phosphate.

[0050] Compared with lithium iron phosphate, lithium manganese iron phosphate replaces some of the Fe elements in the lattice sites with Mn elements, which can greatly increase the charge and discharge voltage of the material, which is beneficial to improve the energy density of the material. However, due to the difference in the radius of manganese and iron ions in lithium manganese iron phosphate, there are gaps between the particles in the lattice, and the compaction density is relatively low (usually 2.2~2.5g / cm 3 By coating lithium nickel manganese oxide with a higher compaction density, the compaction density of the composite positive electrode active material can be significantly improved.

[0051] In some embodiments, the lithium manganese iron phosphate contains at least one of titanium and magnesium.

[0052] Titanium doping can occupy iron or manganese sites, forming stable tetravalent cation centers in the lithium manganese iron phosphate material lattice, improving the material's structural integrity during charge and discharge cycles. Magnesium doping can lengthen the Li-O covalent bond length in the LiO6 octahedron, facilitating lithium ion migration and improving the battery's rate performance.

[0053] In some embodiments, the chemical formula of the lithium manganese iron phosphate is as shown in Formula 1: Li 1+a (Mn x1 Fey1 M1 z1 M2 1-x1-y1-z1 )PO4 formula 1 Among them, -0.2≤a≤0.2, 0<x1<1, 0<y1<1, 0≤z1≤0.05, 0≤1-x1-y1-z1≤0.05; M1 includes at least one of Ti and Mg, and M2 includes at least one of Al, Cu, Zn, Ni, V, Zr, Co, Ga, Sn, Sb, and Nb.

[0054] The above chemical formula can be used to represent the lithium manganese iron phosphate in the positive electrode active material, showing the stoichiometric range of each element and possible doping elements. The fluctuation range of the lithium stoichiometric number (1+a) (-0.2≤a≤0.2) is due to the lithium insertion and removal behavior of the material during the battery's charge and discharge processes. The lithium manganese iron phosphate with the above chemical formula has a well-structured lattice structure and exhibits excellent electrochemical performance.

[0055] The doping elements in lithium manganese iron phosphate can be detected and their chemical formula determined by commonly used methods in the field. For example, 0.2g of positive electrode active material is weighed into a 100mL beaker, 10mL of 10% w / w nitric acid solution is added, and after heating and digesting at 120°C for 0.5 hours, the volume is adjusted to a 100mL volumetric flask; then 1mL is pipetted into a 100mL volumetric flask and the volume is adjusted to obtain a test solution. An inductively coupled plasma optical emission spectrometer (ICP-OES, instrument brand: Agilent 5800) is used to determine the mass fraction of lithium, manganese, iron, phosphorus, doping elements, etc. in the test solution; the molar proportion of each element in the positive electrode active material is calculated based on the mass fraction of each element in the powder test solution, thereby determining the chemical formula and element molar ratio of the positive electrode active material.

[0056] In some embodiments, the particle size Dv50 of the positive electrode active material is 300 nm to 600 nm; for example, it can be about 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, etc.

[0057] When the above Dv50 is adopted, it is more conducive to achieving close packing to improve the compaction density. It is also beneficial to the dispersion of the slurry, has good adaptability to the existing roller pressing process, and has good coating uniformity.

[0058] The particle size Dv50 is well known in the art and refers to the particle size at which 50% of the powder particles are larger than or equal to 50% of the powder particles. It can be measured using instruments and methods well known in the art. For example, it can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer available from Malvern Instruments Ltd., UK.

[0059] In some embodiments, the lithium nickel manganese oxide contains at least one of the following elements: aluminum, phosphorus, and tungsten.

[0060] Aluminum doping improves the material's electronic conductivity. The high Al-O bond energy mitigates structural collapse, reduces Mn dissolution, and forms a stable SEI layer. Phosphorus doping improves the material's surface structural stability and also enhances the surface electronic conductivity of the positive electrode active material. Tungsten doping enhances the material's structural stability, forming a spinel phase on the surface, reducing surface oxygen content, strengthening the chemical bond between transition metals and oxygen, inhibiting the H2-H3 phase transition, and reducing the formation of microcracks.

[0061] In some embodiments, based on the total mass of the core and the first coating layer, the mass proportion of the lithium nickel manganese oxide is 0.8%~2.5%; for example, it can be about 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, etc.

[0062] In general, as the mass proportion of lithium nickel manganese oxide increases, the coating layer formed on the surface of lithium iron manganese phosphate becomes more uniform and stable, which is conducive to improving the compaction density of the composite material. However, the theoretical specific capacity of lithium nickel manganese oxide is lower than that of lithium iron manganese phosphate. Therefore, when the mass proportion of lithium nickel manganese oxide is high, the overall capacity of the composite material will be reduced to a certain extent. When lithium nickel manganese oxide has the above mass proportion, it can better balance the improvement of compaction density and the overall specific capacity of the material.

[0063] In some embodiments, based on the total mass of the core and the first coating layer, the mass of the lithium nickel manganese oxide accounts for 1% to 1.8%.

[0064] When lithium nickel manganese oxide has the above-mentioned mass ratio, it is beneficial to better balance the improvement of compaction density and the overall specific capacity of the material.

[0065] In some embodiments, the positive electrode active material further includes a second coating layer, the second coating layer includes carbon; the second coating layer is disposed on the surface of the first coating layer and / or on the surface of the core not covered by the first coating layer.

[0066] Carbon coating can improve the overall electronic conductivity of the composite material, thereby improving the electrical connection between materials during the battery's charge-discharge cycle, reducing polarization, and improving the material's rate performance. Furthermore, carbon coating reduces direct contact between the active material and the electrolyte, minimizing side reactions; it also mitigates the dissolution of transition metal ions (such as manganese ions) during high-temperature cycling, reducing side reactions caused by transition metal dissolution.

[0067] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of carbon element is 0.8%~2%; for example, it can be about 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, etc.

[0068] When the mass proportion of carbon elements is greater than or equal to 0.8%, the second coating layer has a more obvious effect on improving the overall conductivity of the composite material and can significantly reduce the resistivity of the powder; when the mass proportion of carbon elements does not exceed 2%, the lithium manganese iron phosphate can correspondingly have a higher mass proportion, which is conducive to the composite material having a good gram capacity.

[0069] The carbon content in the positive electrode active material can be determined using methods commonly used in the art. For example, a certain amount (e.g., 1g) of positive electrode active material sample is weighed and placed in the crucible holder of an infrared carbon-sulfur analyzer. Under oxygen-rich conditions, the sample is heated and burned at high temperature in a high-frequency furnace, oxidizing the carbon and sulfur into carbon dioxide and sulfur dioxide. After treatment, the gases enter the corresponding absorption cell, where they absorb the corresponding infrared radiation and are then converted into a corresponding signal by the detector. This signal is sampled by a computer, linearly corrected, and converted into a numerical value proportional to the carbon dioxide and sulfur dioxide concentrations. The values ​​collected throughout the entire analysis process are then accumulated. After the analysis is completed, this accumulated value is divided by the weight in the computer, multiplied by the correction factor, and the blank is subtracted to obtain the carbon percentage in the sample.

[0070] In some embodiments, the powder compaction density of the positive electrode active material under a pressure of 30,000 N is 2.35 g / cm 3 ~2.7g / cm 3 ; For example, it can be about 2.35g / cm 3 , 2.4g / cm 3 , 2.45g / cm 3 , 2.5g / cm 3 , 2.55g / cm 3 , 2.6g / cm 3 , 2.65g / cm 3 , 2.7g / cm 3 wait.

[0071] The positive electrode active material in the embodiment of the present invention has the aforementioned relatively high compaction density, so when used in the positive electrode of a battery, a relatively high positive electrode sheet compaction density can be achieved, which is beneficial for improving the energy density of the battery.

[0072] The compaction density of positive electrode active material powder can be measured using common methods in the art. For example, a certain amount (e.g., 0.6g) of positive electrode active material sample is weighed and placed in a dedicated compaction mold. The mold has a hollow center with two metal discs on each side. The powder is placed between the discs and a metal cylinder is placed on top. The mold is then placed on an electronic pressure testing machine with a pressure of 30,000N. The equipment can read the thickness of the powder at this pressure. The compaction density is then calculated using the formula p = m / V = m / (S × H).

[0073] In some embodiments, the powder resistivity of the positive electrode active material is less than or equal to 80Ω•cm; for example, the powder resistivity may be approximately 80Ω•cm, 70Ω•cm, 60Ω•cm, 50Ω•cm, 40Ω•cm, 30Ω•cm, 20Ω•cm, 10Ω•cm, etc.

[0074] The positive electrode active material in the embodiment of the present invention has the above-mentioned good powder resistivity. When applied to the positive electrode of a battery, it is beneficial to form a good conductive network, reduce polarization, and improve rate performance.

[0075] The powder resistivity of the positive electrode active material can be measured using methods commonly used in the art. For example, a certain amount of sample (e.g., 1 g) is weighed and placed in a mold. The mold is then placed in a four-probe resistivity tester with a pressure of 8.0 MPa. After the mold height and pressure stabilize, the forward and reverse resistivity of the sample are measured, and the average of the two values ​​is taken as the powder resistivity of the sample.

[0076] Preparation of positive electrode active materials In some embodiments, the lithium iron manganese phosphate is first added to a high-speed mixer according to the mass ratio of the lithium iron manganese phosphate core to the lithium nickel manganese oxide coating layer. The lithium nickel manganese oxide is then added to the mixer according to the molar ratio of the elements. After uniform mixing, the resulting powder is sintered at a high temperature to prepare a positive electrode active material having a lithium iron manganese phosphate core and a first coating layer formed of lithium nickel manganese oxide. When the lithium nickel manganese oxide contains a doping element, a precursor of the doping element can be added according to the corresponding molar ratio of the elements.

[0077] In some embodiments, according to the mass ratio of the lithium iron manganese phosphate core to the lithium nickel manganese oxide coating, the jet-milled lithium iron manganese phosphate is first added to a high-speed mixer, and the lithium nickel manganese oxide is added to the high-speed mixer according to the molar ratio of the elements. After uniform mixing, the resulting powder is placed in a sagger and placed in a box furnace. The furnace is heated to 900-950°C at a heating rate of 2-3°C / min and kept warm for 8-10 hours. The lithium nickel manganese oxide heterogeneously nucleates on the surface of the lithium iron manganese phosphate. After cooling, the cathode active material is taken out to obtain a lithium iron manganese phosphate core with a first coating layer formed by lithium nickel manganese oxide. The lithium source can be one or more of lithium carbonate, lithium oxalate, and lithium hydroxide; the nickel source can be one or more of NiO, Ni2O3, and Ni3O4; and the manganese source can be one or more of MnO, Mn2O3, MnO2, and Mn3O4.

[0078] In some embodiments, lithium manganese iron phosphate can be co-doped with elements such as titanium and magnesium through a high-temperature solid-phase sintering process. For example, for co-doping with titanium and magnesium, lithium, manganese, iron, titanium, and magnesium sources are weighed according to the molar ratio of each element in the target material and added to a reactor filled with deionized water, where they are thoroughly stirred. The stirring rate is controlled at 200-300 rpm, and the mixture is stirred for 2-3 hours to obtain a slurry. The slurry is then passed through a sand mill and ground using 0.6-0.8 mm zirconium beads for 3-4 hours. The ground slurry is spray-dried in a spray dryer with an inlet temperature of 180-200°C and an outlet temperature of 110-120°C to obtain a powder. The powder is then placed in a sagger, placed in a box furnace, and heated to 650-700°C at a heating rate of 3-5°C / min. The mixture is then held at this temperature for 8-10 hours. After cooling, the material is removed from the furnace to obtain a titanium- and magnesium-co-doped lithium manganese iron phosphate material. Among them, the lithium source can be one or more of lithium carbonate, lithium oxalate, and lithium hydroxide; the phosphorus source can be one or more of phosphoric acid, ferric phosphate, ferrous phosphate, ammonium ferrous phosphate, ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, ammonium phosphate, lithium monohydrogen phosphate, and lithium dihydrogen phosphate; the iron source can be one or more of ferric hydroxide, ferric oxide, ferrous oxide, ferrous phosphate, ferrous phosphate, ferrous oxalate, ferric acetate, and ferric sulfate; the manganese source can be one or more of manganese nitrate, manganese acetate, manganese phosphate, manganese oxalate, manganese carbonate, and ammonium manganese phosphate; the doping element magnesium source is one or more of magnesium oxide, magnesium acetate, and magnesium carbonate; the titanium source is one or more of titanium dioxide, titanium sulfate, lithium titanate, and iron titanate.

[0079] In some embodiments, a positive electrode active material having a core of lithium manganese iron phosphate and having a first coating layer and a second coating layer can be prepared according to the following method. First, a positive electrode active material having a core of lithium manganese iron phosphate and a first coating layer of lithium nickel manganese oxide is prepared according to the aforementioned method, and then carbon coating is performed by chemical vapor deposition (CVD). For example, the positive electrode active material having a core of lithium manganese iron phosphate and a first coating layer formed of lithium nickel manganese oxide can be placed in a carbon-coated rotary kiln, and an inert gas is introduced for gas washing. After two hours of gas washing, the rotary kiln is heated at a certain heating rate, and the inert gas is continued to be introduced to maintain the gas pressure in the kiln at a slightly positive pressure. After the rotary kiln is heated to a specified temperature, the introduction of the inert gas is stopped, and the introduction of a gaseous carbon source is started, and the gas pressure in the kiln is maintained at a slightly positive pressure. The material is subjected to high-temperature CVD carbon coating for a certain period of time under a continuous flow atmosphere. After the high-temperature CVD carbon coating is completed, the heating power is turned off and the introduction of the gaseous carbon source is stopped, thereby obtaining a positive electrode active material having a core of lithium manganese iron phosphate and a first coating layer and a second coating layer. The gaseous carbon source can be one or more combinations of methane, ethylene, acetylene, propane, methanol, ethanol, propylene, butane, and butene.

[0080] battery cells In the embodiment of the present application, the battery cell may be a secondary battery. A secondary battery refers to a battery cell that can be continuously used by activating active materials by charging after the battery cell is discharged.

[0081] In the embodiment of the present application, the battery cell may be a lithium-ion battery.

[0082] [Electrode assembly] A battery cell typically includes an electrode assembly. This assembly includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator, which is positioned between the positive and negative electrodes. During the charge and discharge process of the battery cell, active ions (such as lithium ions) move back and forth between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, prevents short circuits between the positive and negative electrodes while allowing the active ions to pass through.

[0083] [Positive electrode] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector; The positive electrode material layer includes the positive electrode active material described in any embodiment of the present application.

[0084] As previously mentioned, the positive electrode active material provided in the embodiments of this application has excellent compaction density. When a battery cell utilizes this positive electrode active material, a high positive electrode material layer compaction density can be achieved, thereby achieving good energy density. Furthermore, when this positive electrode active material exhibits other advantages, the battery cell also exhibits correspondingly excellent performance.

[0085] In some embodiments, the compaction density of the positive electrode material layer is 2.3-2.5 g / cm 3 ; For example, it can be about 2.3g / cm 3 , 2.35g / cm 3 , 2.4g / cm 3 , 2.45g / cm 3 , 2.5g / cm 3 wait.

[0086] By adopting the aforementioned positive electrode active material, the positive electrode material layer can have the above-mentioned compaction density, which is beneficial for the battery to have excellent energy density.

[0087] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymer substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0088] The positive electrode active material may also include at least one of the following materials: lithium-containing phosphates, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium-containing phosphates may include but are not limited to at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. Examples of lithium transition metal oxides may include but are not limited to lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.8 Co 0.15 Al 0.05 O2) and at least one of its modified compounds. Modified compounds refer to substances obtained by modifying the above substances through methods such as doping or coating.

[0089] In some embodiments, the positive electrode material layer may further optionally include a binder. For example, the binder may include one or a combination of two or more of the following: polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0090] In some embodiments, the positive electrode material layer may further include a conductive agent. For example, the conductive agent may include one or a combination of two or more of the following: Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0091] In some embodiments, the positive electrode sheet can be prepared by the following method: dispersing the components of the above-mentioned positive electrode material layer, such as the positive electrode active material, the chelating agent, the optional conductive agent, the optional binder and any other components in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry on the positive electrode collector, and obtaining the positive electrode sheet after drying, cold pressing and other processes.

[0092] [Negative electrode] The negative electrode sheet includes a negative electrode active material. In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode material layer includes a negative electrode active material.

[0093] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil or copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymer substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0094] In some embodiments, the negative electrode active material layer may use negative electrode active materials for lithium ion batteries known in the art. For example, the negative electrode active material includes one or a combination of two or more selected from the following groups: natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, TiO2-Li4Ti5O 12 , Li-Al alloy.

[0095] In some embodiments, the negative electrode material layer may further include a binder. For example, the binder may include one or a combination of two or more selected from the group consisting of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0096] In some embodiments, the negative electrode material layer may further include a conductive agent. For example, the conductive agent may include one or a combination of two or more selected from the group consisting of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0097] In some embodiments, the negative electrode material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0098] In some embodiments, the negative electrode sheet can be prepared by the following method: dispersing the components of the above-mentioned negative electrode material layer, such as the negative electrode active material, the conductive agent, the binder and any other components in a solvent (such as deionized water) to form a negative electrode slurry; coating the negative electrode slurry on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0099] [Electrolytes] In some embodiments, the battery cell further includes an electrolyte, which acts as a conductor of ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and the electrolyte may be selected based on specific needs. The electrolyte may be liquid, gel, or solid.

[0100] The liquid electrolyte includes an electrolyte salt and a solvent.

[0101] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0102] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone. The solvent can also be an ether solvent. Ether solvents can include one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether and crown ether.

[0103] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives capable of improving certain properties of the battery cell, such as additives that improve the overcharge / fast charge performance of the battery cell, additives that improve the high-temperature performance of the battery cell, and additives that improve the low-temperature performance of the battery cell.

[0104] Among them, the gel electrolyte includes a polymer as a skeleton network and can be used in combination with an ionic liquid-lithium salt.

[0105] Among them, solid electrolytes include polymer solid electrolytes, inorganic solid electrolytes, and composite solid electrolytes.

[0106] As an example, the polymer of the polymer solid electrolyte may include polyether (polyethylene oxide), polysiloxane, polycarbonate, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, a single ion polymer, a polyionic liquid, cellulose, and the like.

[0107] As an example, the inorganic solid electrolyte can be an oxide solid electrolyte (crystalline perovskite, sodium superconducting ion conductor, garnet, amorphous LiPON film), a sulfide solid electrolyte (crystalline lithium superion conductor (lithium germanium phosphide, germanium sulfide silver), amorphous sulfide) and one or more of a halide solid electrolyte, a nitride solid electrolyte and a hydride solid electrolyte.

[0108] As an example, a composite solid electrolyte is formed by adding an inorganic solid electrolyte filler to a polymer solid electrolyte.

[0109] [Isolator] In some embodiments, the electrode assembly further includes a separator disposed between the positive electrode sheet and the negative electrode sheet.

[0110] In some embodiments, the separator is a separator. The present application has no particular limitation on the type of separator, and any known separator with a porous structure having good chemical and mechanical stability can be selected.

[0111] As an example, the primary material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, polyvinylidene fluoride, and ceramic. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation. The separator can be a separate component located between the positive and negative electrodes, or it can be attached to the surfaces of the positive and negative electrodes. The surface of the separator can also be coated with an inorganic particle coating, an organic particle coating, or an organic / inorganic composite coating.

[0112] In some embodiments, the separator is a solid electrolyte, which is disposed between the positive electrode and the negative electrode and serves to transport ions and isolate the positive and negative electrodes.

[0113] [Structure of the electrode assembly] The electrode assembly may be a wound structure, a laminated structure, or a mixed structure of wound and laminated structures.

[0114] In some embodiments, the electrode assembly is a wound structure, wherein the positive electrode sheet and the negative electrode sheet are wound into the wound structure.

[0115] In some embodiments, the electrode assembly is a laminate structure.

[0116] As an example, multiple positive electrode sheets and multiple negative electrode sheets can be provided respectively, and the multiple positive electrode sheets and the multiple negative electrode sheets can be alternately stacked.

[0117] As an example, multiple positive electrode sheets may be provided, and the negative electrode sheet is folded to form multiple stacked folded segments, with a positive electrode sheet sandwiched between adjacent folded segments.

[0118] As an example, both the positive electrode sheet and the negative electrode sheet are folded to form a plurality of stacked folded segments.

[0119] As an example, multiple separators may be provided, each of which is provided between any adjacent positive electrode sheets or negative electrode sheets.

[0120] As an example, the separator may be provided continuously, and may be provided between any adjacent positive electrode sheets or negative electrode sheets by folding or winding.

[0121] In some embodiments, the shape of the electrode assembly can be cylindrical, flat, or polygonal.

[0122] In some embodiments, the electrode assembly is provided with tabs that can conduct current from the electrode assembly. The tabs include a positive tab and a negative tab.

[0123] [shell] In some embodiments, a battery cell may include an outer shell. This outer shell may be a steel shell, an aluminum shell, a plastic shell (such as polypropylene), a composite metal shell (such as a copper-aluminum composite shell), or an aluminum-plastic film. In some embodiments, the outer shell may be sealed or non-sealed. For example, in a non-sealed outer shell, the outer shell protects the electrode assembly and includes a sealing bag between the outer shell and the electrode assembly, which encapsulates the electrode assembly and electrolyte. Specifically, the sealing bag may be a bag-shaped insulating member or an aluminum-plastic film. In a sealed outer shell, the outer shell encapsulates the electrode assembly, electrolyte, and other components.

[0124] As an example, the battery cell can be a cylindrical battery cell, a prismatic battery cell, a soft-pack battery cell or a battery cell of other shapes. The prismatic battery cell includes a square-shell battery cell, a blade-shaped battery cell, a multi-prismatic battery, and a multi-prismatic battery such as a hexagonal battery. There is no particular limitation in this application. For example, Figure 1 The battery cell 5 is a square case as an example.

[0125] In some embodiments, reference Figure 2 The outer shell includes an end cap 53 and a housing 51. The housing 51 has an opening, and the end cap 53 covers the opening. The housing 51 may have one or more openings. One or more end caps 53 may also be provided. The positive electrode sheet, the negative electrode sheet, and the separator may be wound or laminated to form an electrode assembly 52. ​​The electrode assembly 52 is enclosed in a housing formed by the housing 51 and the end cap 53. The electrolyte is impregnated in the electrode assembly 52.

[0126] [Electrode terminal] In some embodiments, the housing is provided with at least one electrode terminal, which is electrically connected to the tab. The electrode terminal may be directly connected to the tab or indirectly connected to the tab via a current collecting member. The electrode terminal may be provided on an end cap or on the housing.

[0127] [Pressure relief mechanism] In some embodiments, the housing is provided with a pressure relief mechanism for discharging internal gas of the battery cell.

[0128] For example, when the internal pressure or temperature of a battery cell reaches a predetermined threshold, the pressure relief mechanism activates to release the internal pressure or temperature. When the internal pressure or temperature of the battery cell reaches the predetermined threshold, the pressure relief mechanism activates or a weak structure within the pressure relief mechanism is destroyed, thereby forming an opening or channel for the internal pressure or temperature to be released. The threshold design varies depending on the design requirements. The threshold may depend on the material of one or more of the positive electrode sheet, negative electrode sheet, electrolyte, and separator in the battery cell.

[0129] As an example, the pressure relief mechanism may be integrally formed with the housing.

[0130] As an example, the pressure relief mechanism may also be provided separately from and connected to the housing.

[0131] The "activation" mentioned in this application refers to the action of the pressure relief mechanism or its activation to a certain state, so that the internal pressure and temperature of the battery cell can be released. The action produced by the pressure relief mechanism may include but is not limited to: the movement of components in the pressure relief mechanism to form an exhaust channel, at least a part of the pressure relief mechanism rupturing, breaking, tearing or opening, etc. When the pressure relief mechanism is actuated, the high-temperature and high-pressure substances inside the battery cell will be discharged outward from the actuated part as emissions. In this way, the pressure and temperature of the battery cell can be relieved under controllable pressure or temperature, thereby avoiding potential more serious accidents.

[0132] In some embodiments, when the outer shell is a non-sealed structure, the pressure relief mechanism can be configured as a through hole for discharging gas from inside the battery cell.

[0133] The emissions from the battery cells mentioned in this application include but are not limited to: electrolyte, dissolved or split positive and negative electrode sheets, fragments of separators, high-temperature and high-pressure gases generated by the reaction, flames, etc.

[0134] Battery device The battery apparatus mentioned in the embodiments of the present application may include one or more battery cell assemblies for providing voltage and capacity. The battery cell assembly may include multiple battery cells, which are connected in series, parallel, or hybrid via a busbar.

[0135] In some embodiments, a battery cell assembly is generally formed by arranging a plurality of battery cells.

[0136] As an example, the battery cell assembly may be a battery module, which is formed by arranging and fixing multiple battery cells to form an independent module. As an example, the battery module may be formed by bundling multiple battery cells with a cable tie. Figure 3 This is a battery module 4 as an example. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner.

[0137] In some embodiments, the battery device may be a battery pack, which includes a case and one or more battery cell assemblies, wherein the battery cell assemblies are housed in the case.

[0138] As an example, the battery cell assembly may be a battery module, and the battery cell assembly may be accommodated in the box by fixing the battery module in the box. Figure 4 and Figure 5 The battery pack 1 is used as an example. Figure 4 and Figure 5 The battery pack 1 may include a case and multiple battery modules 4 disposed therein. The case includes an upper case 2 and a lower case 3. The upper case 2 can cover the lower case 3 and form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery case.

[0139] As an example, the battery cell assembly may also be housed in the box by directly fixing the plurality of battery cells to the box.

[0140] As an example, the housing may include a first housing and a second housing. The first housing and the second housing engage to form an enclosed space within the housing to house the battery cell assembly. Enclosed here means covered or closed, and can be either sealed or unsealed. The first housing may be a top cover or a bottom plate.

[0141] As an example, the box may include a top cover, a frame, and a bottom plate, wherein the top cover and the bottom plate are respectively connected to the frame to form a closed space inside the box to accommodate the battery cell assembly.

[0142] In some embodiments, the box body can be used as a part of the chassis structure of the vehicle. For example, part of the box body can become at least a part of the floor of the vehicle, or part of the box body can become at least a part of the cross beam and longitudinal beam of the vehicle.

[0143] Electrical devices The technical solutions described in the embodiments of the present application are applicable to various electrical devices that use battery cells, such as mobile phones, portable devices, laptop computers, electric vehicles, electric toys, electric tools, vehicles, ships and spacecraft, for example, spacecraft include airplanes, rockets, space shuttles and spacecraft, etc. Figure 6 The power consumption device is taken as an example, and the power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.

[0144] Example 1 This embodiment provides a positive electrode active material and a lithium-ion battery.

[0145] 1. Preparation of positive electrode active materials The positive electrode active material is composed of titanium and magnesium co-doped lithium manganese iron phosphate as the core, which is coated with lithium nickel manganese oxide and carbon coating layer in sequence. The specific preparation method is as follows: (1) According to the chemical formula of titanium and magnesium co-doped lithium manganese iron phosphate (LiMn 0.6 Fe 0.36 Ti 0.02 Mg 0.02 FePO4, MnC2O4, Li2CO3, NH4H2PO4, TiO2 and MgO were weighed and added to a reactor filled with deionized water for thorough stirring. The stirring rate was controlled at 300 rpm and stirred for 2 hours to obtain a slurry. The slurry was passed into a sand mill for grinding and ground with 0.6~0.8mm zirconium beads for 3 hours. The ground slurry was spray dried in a spray dryer with an inlet temperature of 200°C and an outlet temperature of 110°C to obtain a powder. The powder was loaded into a sagger, placed in a box furnace, heated to 650°C at a heating rate of 5°C / min, kept warm for 8 hours, and taken out after cooling to obtain a titanium and magnesium co-doped lithium manganese iron phosphate material; (2) Use jet milling to treat the titanium and magnesium co-doped lithium manganese phosphate material obtained in step (1). The jet milled lithium manganese phosphate is added to the high-pressure mixer according to the mass ratio of lithium manganese phosphate core to lithium nickel manganese oxide coating layer of 98.6:1.4, and lithium nickel manganese oxide is mixed according to the molar ratio of its elements (LiNi 0.5Mn 1.5 O4) Lithium source, manganese source and nickel source are put into a high-speed mixer and mixed at 1000r / min, 1500r / min and 2000r / min for ten minutes respectively. After mixing evenly, the powder is put into a sagger and placed in a box furnace. The mixture is heated to 900°C at a heating rate of 2°C / min and kept warm for 10 hours to allow lithium nickel manganese oxide to be coated on the surface of lithium iron manganese phosphate through heterogeneous nucleation. After cooling, the material is taken out to obtain lithium nickel manganese oxide-coated titanium and magnesium co-doped lithium iron manganese phosphate material.

[0146] (3) The titanium and magnesium co-doped lithium manganese iron phosphate material coated with lithium nickel manganese oxide obtained in step (2) is placed in a rotary kiln and nitrogen is introduced for gas washing. After two hours of gas washing, the rotary kiln is heated at a heating rate of 5°C / min and nitrogen is continuously introduced. The pressure in the furnace is kept at a slightly positive pressure during the whole process. When the rotary kiln is heated to 1000°C, the nitrogen is stopped and a mixed gas is started. The mixed gas composition is 20% methane and 80% argon. The pressure in the furnace is kept at a slightly positive pressure. The material is carbon-coated in a continuously flowing methane atmosphere for 5 hours. After the coating is completed, the heating power is turned off and the introduction of the mixed gas is stopped. The temperature in the furnace is lowered to room temperature to obtain a positive electrode active material with lithium manganese iron phosphate co-doped with titanium and magnesium as the core and coated with lithium nickel manganese oxide and a carbon coating layer in sequence. The TEM image of the positive electrode active material is shown in FIG. Figure 7 As shown, the particle size Dv50 is 450nm, the mass percentage of carbon element is 1.2%, and the powder compaction density under a pressure of 30000N is 2.552g / cm 3 , the powder resistivity is 30Ω•cm.

[0147] 2. Preparation of button lithium-ion batteries

Positive electrode

[0148]

Counter electrode

[0149] [Electrolyte] The electrolyte LiPF6 was dissolved in a mixed solvent of ethylene carbonate / dimethyl carbonate (EC / DMC) with a volume ratio of 1:1 to form an electrolyte.

[0150]

Isolation film

[0151]

Preparation of button lithium-ion battery

[0152] Perform the following tests and record the test results in Table 1: 1. Test of charge and discharge gram ratio capacity Testing was performed using a Wuhan Landian (LAND2001A) electrochemical performance tester. The assembled battery was left for 12 hours to allow the electrolyte to fully soak into the negative electrode. The battery was then clamped to the tester's alligator clips. The test current, active material mass, and test voltage range were input, and the tester automatically displayed the battery's charge and discharge specific capacities. The test voltage range was 0.01-2V, the current density was 100mA / g, and the test current = current density × active material mass. The active material mass = slurry mass × 80%, and the slurry mass = wafer mass - blank collector mass.

[0153] 2. Test of capacity retention at 25℃ Shenzhen Xinweier battery testing system was used to cycle button batteries at a charge and discharge rate of 1C for 1000 times. The test temperature was 25.0℃, and the charge and discharge voltage was 2.0V~4.3V. The capacity retention rate was calculated by dividing the discharge capacity of the last cycle by the discharge capacity of the first cycle.

[0154] Comparative Example 1 Except for the lack of the lithium nickel manganese oxide coating layer, that is, the lack of step (2), the preparation and testing were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0155] Examples 2 to 5 Except for changing the mass ratio of the lithium manganese iron phosphate core and the lithium nickel manganese oxide coating layer, as shown in Table 1, the same steps as in Example 1 were followed for preparation and testing. The results are shown in Table 1.

[0156] In Table 1, the “mass proportion of the lithium nickel manganese oxide coating layer” is calculated based on the sum of the masses of the lithium iron manganese phosphate core and the lithium nickel manganese oxide coating layer.

[0157] Table 1

[0158] By comparing Examples 1 to 5 and Comparative Example 1, it can be seen that the powder compaction density of the positive electrode active material is improved by applying the lithium nickel manganese oxide coating layer. By comparing Examples 1 to 5, it can be seen that, on the one hand, when the mass proportion of the lithium nickel manganese oxide coating layer is higher, the improvement effect on the compaction density is more obvious. On the other hand, the mass proportion of the lithium nickel manganese oxide coating layer also affects the charge and discharge gram capacity. When its mass proportion is low (for example, Example 2), it may be difficult to form a uniform and stable coating on the surface of lithium iron manganese phosphate due to the small amount of lithium nickel manganese oxide used, resulting in an unsatisfactory capacity release effect of the composite positive electrode active material; when its mass proportion is high (for example, Example 5), the mass proportion of lithium iron manganese phosphate is reduced accordingly, and the theoretical specific capacity of lithium nickel manganese oxide is lower than that of lithium iron manganese phosphate, which leads to a decrease in the overall capacity of the material. Therefore, when the mass proportion of the lithium nickel manganese oxide coating layer is between 1% and 1.8%, it has a more balanced improvement effect in improving the powder compaction density and charge and discharge gram capacity.

[0159] Examples 6 to 10 The preparation and testing were carried out according to the same steps as in Example 1, except that the amount of the precursor was changed so that the stoichiometric ratio of the doping elements in the lithium manganese iron phosphate was as shown in Table 2. The results are shown in Table 2.

[0160] Table 2

[0161] Based on the above results, combined with principle analysis, it can be seen that the titanium doping level mainly affects the structural stability of the material, and thus mainly affects the improvement of capacity retention. The magnesium doping level mainly affects the rate performance of the battery, which may be due to the fact that the addition of magnesium changes the lithium ion transmission path. By doping with magnesium and titanium, the battery's rate performance and cycle capacity retention are improved. Further optimizing the doping levels of the two elements can achieve significantly better results.

[0162] Examples 11-12 The same preparation and testing procedures as in Example 1 were followed, except that the time for introducing the mixed gas in the carbon coating step was adjusted so that the carbon content was as shown in Table 3. The results are shown in Table 3.

[0163] In Table 3, the carbon content was calculated based on the total mass of the positive electrode active material.

[0164] Table 3

[0165] Examples 13-14 The preparation and testing were carried out in the same manner as in Example 1, except that the particle size of the inner core was adjusted so that the particle size Dv50 of the positive electrode active material was as shown in Table 4, and the powder compaction density of the positive electrode active material and the compaction density of the positive electrode material layer were as shown in Table 4. The results are shown in Table 4.

[0166] Table 4

[0167] The above description is merely a preferred embodiment of the present application, but the scope of protection of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in this application should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of protection of the claims.

Claims

1. A positive electrode active material, characterized in that The positive electrode active material includes a core and a first coating layer disposed on at least a portion of the surface of the core; The core includes a lithium-containing phosphate; The first coating layer includes lithium nickel manganese oxide.

2. The positive electrode active material according to claim 1, wherein The lithium-containing phosphate includes lithium manganese iron phosphate.

3. The positive electrode active material according to claim 2, wherein The lithium manganese iron phosphate contains at least one of titanium and magnesium.

4. The positive electrode active material according to claim 2, wherein The chemical formula of the lithium manganese iron phosphate is shown in Formula 1. Li 1+a (Mn x1 Fe y1 M1 z1 M2 1-x1-y1-z1 )PO₄ formula 1 Among them, -0.2≤a≤0.2, 0<x1<1, 0<y1<1, 0≤z1≤0.05, 0≤1-x1-y1-z1≤0.05; M1 includes at least one of Ti and Mg, and M2 includes at least one of Al, Cu, Zn, Ni, V, Zr, Co, Ga, Sn, Sb, and Nb.

5. The positive electrode active material according to claim 1, wherein The particle size Dv50 of the positive electrode active material is 300nm~600nm.

6. The positive electrode active material according to claim 1, wherein The lithium nickel manganese oxide contains at least one of the following elements: aluminum, phosphorus, and tungsten.

7. The positive electrode active material according to claim 1, wherein Based on the total mass of the core and the first coating layer, the mass of the lithium nickel manganese oxide accounts for 0.8% to 2.5%.

8. The positive electrode active material according to claim 7, wherein Based on the total mass of the core and the first coating layer, the mass of the lithium nickel manganese oxide accounts for 1% to 1.8%.

9. The positive electrode active material according to claim 1, wherein The positive electrode active material further includes a second coating layer, which includes carbon; the second coating layer is arranged on the surface of the first coating layer and / or on the surface of the core not covered by the first coating layer.

10. The positive electrode active material according to claim 9, characterized in that Based on the total mass of the positive electrode active material, the mass percentage of carbon element is 0.8% to 2%.

11. The positive electrode active material according to any one of claims 1 to 10, wherein The powder compaction density of the positive electrode active material under a pressure of 30,000 N is 2.35 g / cm 3 ~2.7g / cm 3 .

12. The positive electrode active material according to any one of claims 1 to 10, wherein The powder resistivity of the positive electrode active material is less than or equal to 80Ω·cm.

13. A battery cell, characterized in that: It comprises a positive electrode sheet, an electrolyte and a negative electrode sheet; the positive electrode sheet comprises a positive electrode collector and a positive electrode material layer arranged on at least one surface of the positive electrode collector; the positive electrode material layer comprises the positive electrode active material according to any one of claims 1 to 12.

14. The battery cell according to claim 13, wherein: The compaction density of the positive electrode material layer is 2.3 g / cm 3 ~2.5g / cm 3 .

15. A battery device, characterized in that: Comprising the battery cell according to claim 13 or 14.

16. An electrical device, characterized in that: Comprising the battery cell according to claim 13 or 14, or the battery device according to claim 15.

Citation Information

Patent Citations

  • Lithium iron manganese phosphate composite material and preparation method and application thereof

    CN111697203A

  • Lithium iron manganese phosphate powder material as well as preparation method and application thereof

    CN111710846A

  • Lithium manganese iron phosphate precursor, lithium manganese iron phosphate positive electrode material, preparation method of lithium manganese iron phosphate positive electrode material, electrode material, electrode and lithium ion battery

    CN113942990A

  • Composite lithium manganese iron phosphate material as well as preparation method and application thereof

    CN116169274A

  • Positive electrode material and preparation method and application thereof

    CN116632215A